Nuclear excitation at the positron annihilation taking into account the radiative corrections - S. N. Fedotkin; V. A. Zheltonozhskii (Âderna Fìzika ta Energetika, 2006)
The process of nuclear excitation at the positron-atomic electron annihilation was considered. The relative contribution nonradiative versus radiative was analysed. It is offered a new definition for the share positrons, which excite a nuclei at the annihilation. As result, it is proposed the new interpretation of the experimental date if we compare them with the theoretical calculations.